Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico - Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Zaldívar-Riverón, Alejandro; Correa-Sandoval, Alfonso (Zootaxa, 2016)
The present contribution describes five new species of Phaneropterinae from Northeastern Mexico: Obolopteryx eurycerca n. sp., Barrientos-Lozano & Rocha-Sánchez, O. nigra n. sp., Barrientos-Lozano & Rocha-Sánchez, O. tamaholipana n. sp., Barrientos-Lozano & Rocha-Sánchez, O. huastecana n. sp., Barrientos-Lozano & Rocha-Sánchez, and O. tanchipae n. sp., Barrientos-Lozano & Rocha-Sánchez. Diagnostic characters are illustrated and information on distribution and ecology provided. Polymorphism and geographic variation of the genus Obolopteryx Cohn et al. 2014 are discussed.